Aquagenic wrinkling of the palms: A report of two cases from a family medicine setting in Eastern Saudi Arabia and literature review - Maryam K. Alsoweilem; Rasha H. Alsheikh (Journal of Family and Community Medicine)
Aquagenic wrinkling of the palms (AWP) is a rare transient dermatological disorder, characterized by an extreme and early wrinkling and pruning of the palms that occurs within a few minutes of exposure to water. Greater awareness of AWP is needed since the vast majority of AWP cases are linked with cystic fibrosis (CF) and CF carrier state. Initial assessment of AWP cases can be done in a primary care setting. A comprehensive medical history and physical examination should be done upon the diagnosis of AWP with additional investigations based on patients’ presentation. We report two cases of AWP diagnosed at a family medicine center in Dammam, Saudi Arabia. The first case was related to the use of ibuprofen and discounting this medication led to a marked improvement in the patient’s symptoms. The second case was related to primary palmar hyperhidrosis that was managed successfully with topical 20% aluminum chloride.